2020
DOI: 10.48550/arxiv.2005.13550
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Testing the Evolution of the Correlations between Supermassive Black Holes and their Host Galaxies using Eight Strongly Lensed Quasars

Xuheng Ding,
Tommaso Treu,
Simon Birrer
et al.

Abstract: One of the main challenges in using high redshift active galactic nuclei to study the correlations between the mass of the supermassive Black Hole (M BH ) and the properties of their active host galaxies is instrumental resolution. Strong lensing magnification effectively increases instrumental resolution and thus helps to address this challenge. In this work, we study eight strongly lensed active galactic nuclei (AGN) with deep Hubble Space Telescope (HST) imaging, using the lens modelling code L to reconstru… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…It has also been shown that some properties of source galaxies can be recovered to sufficient precision without using pixel-level modelling (e.g. for deriving AGN mass-luminosity relation, Ding et al 2020a). However, for certain applications that require insights on small-scale features in source galaxies, such as the study of star-forming regions (e.g.…”
Section: Source Reconstruction Of Slacs Lensesmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been shown that some properties of source galaxies can be recovered to sufficient precision without using pixel-level modelling (e.g. for deriving AGN mass-luminosity relation, Ding et al 2020a). However, for certain applications that require insights on small-scale features in source galaxies, such as the study of star-forming regions (e.g.…”
Section: Source Reconstruction Of Slacs Lensesmentioning
confidence: 99%
“…Strongly lensed quasars are particularly useful to constrain black hole evolution over a wide range of redshifts (e.g. Ding et al 2020a) and to derive high-precision constraints on the Hubble constant (Wong et al 2019;Shajib et al 2020a;Birrer et al 2020, now referred as the TDCOSMO collaboration). All of the above applications require lens modelling tools.…”
Section: Introductionmentioning
confidence: 99%
“…They can be used to measure the initial mass function (IMF) and dark-matter substructures in the lensing galaxies (e.g., Mao & Schneider 1998;Metcalf & Madau 2001;Dalal & Kochanek 2002;Pooley et al 2009;Nierenberg et al 2014;Oguri et al 2014;Schechter et al 2014;Jiménez-Vicente & Mediavilla 2019). They also serve as a unique probe of the size and temperature profile of black hole accretion discs and black hole/host galaxy scaling relations at cosmological distances (e.g., Peng et al 2006;Ding et al 2017;Bate et al 2018;Morgan et al 2018;Ding et al 2020). The statistics of a well-defined sample of strongly-lensed QSOs can provide a simple and robust constraint on the structure growth and hence dark energy (e.g., Chae 2007; Oguri et al 2008Oguri et al , 2012.…”
Section: Introductionmentioning
confidence: 99%